2022
DOI: 10.34007/jehss.v5i2.1314
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Spiritualitas dan Dukungan Sosial dengan Resiliensi Mahasiswa Sekolah Tinggi Diakones HKBP

Abstract: Empirically, this study aims to see the correlation between spirituality and social support with the resilience of HKBP Deaconess School Students. The population in this study was 120 people and the sample was 92 people where the sample was taken using random sampling. This type of research is a quantitative research with multiple regression analysis technique where the data collection uses questionnaire that is processed by the SPSS program. The results showed that:(1) There is a significant positive correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…Thus, having high spirituality and receiving social support from those around can influence the resilience of LDM congregants in HKBP District XVIII Jabartengdiy. This is supported by previous research by Caton (2021) [8] and Malau et al (2022) [14] , which revealed that spirituality and social support can predict an individual's resilience. Individuals with strong spirituality and social support tend to have higher resilience, while those with low spirituality and social support tend to have lower resilience.…”
Section: Social Support As a Predictor Of Resilience In Long Distance...supporting
confidence: 85%
See 1 more Smart Citation
“…Thus, having high spirituality and receiving social support from those around can influence the resilience of LDM congregants in HKBP District XVIII Jabartengdiy. This is supported by previous research by Caton (2021) [8] and Malau et al (2022) [14] , which revealed that spirituality and social support can predict an individual's resilience. Individuals with strong spirituality and social support tend to have higher resilience, while those with low spirituality and social support tend to have lower resilience.…”
Section: Social Support As a Predictor Of Resilience In Long Distance...supporting
confidence: 85%
“…Aspects of social support according to Sarafino and Smith (in Candrakanti & Chusairi, 2023) [7] include emotional support, instrumental support, informational support, and social network support. Previous research by Caton (2021) [8] and Malau et al (2022) [14] also revealed that spirituality and social support can predict a person's resilience. This means that individuals with strong spirituality and social support have high resilience.…”
Section: Introductionmentioning
confidence: 89%
“…Resiliensi merupakan faktor yang berkontribusi terhadap flourishing [20]. Hal tersebut dipertegas oleh pendapat ahli sebelumnya bahwa perkembangan flourishing terjadi karena individu memiliki kemampuan resiliensi dalam beradaptasi dengan kondisi di lingkungan [21]. Sejauh ini resiliensi merupakan anteseden untuk flourishing [22].…”
Section: Pendahuluanunclassified